(untitled) (Indian Journal of Animal Production and Management, 2014)
Seven rations (six complete rations were formulated by using sugarcane by products and other crop residues and balanced concentrate mixture in the mash form and one conventional ration comprised with hybrid Napier and concentrate mixture) were prepared and fed to 28 Murrah buffaloes for a period of 180 days using Randomized Block Design to study the effect of processing of complete diet on nutrient utilization and milk production. The DMI (kg/100kgbody wt) was significantly (P<0.01) higher in buffaloes fed on complete rations than on control. The DCP and TDN contents were significantly (P<0.01) higher in complete rations, when compared to control ration. The digestibility coefficients of proximate nutrients (P<0.01) and cell wall fractions (P<0.05) were significantly higher in buffaloes fed with complete rations than those fed on conventional diet. The milk yields of buffaloes were 11.60 1.60,11.90 1.05,12.25 0.59,11.85 0.65,12.05 0.44, 11.80 0.91 and 9.20 0.46 kg in buffaloes fed with CR-I, II, III, IV, V, VI and control, respectively though insignificant. However, 6% FCM yields were significantly (P<0.05) higher in buffaloes fed on complete rations when compared to conventional diet. The cost per kg sugarcane by-product and other crop residue based complete ration was ranged from Rs.2.73 to 3.41.The cost per kg complete ration was lower by 10.24, 14.28 and 11.42 percentage units in CR-IV, V and VI rations, respectively when compared to control ration (Rs.3.12).